An approach for verifying correctness of web service compositions - Saranya Jothi, C.; S, Ravikumar; Kumar K, Antony; Suresh, A. (International Journal of Engineering and Technology, 2018)
Web services are utilized to illuminate some particular assignment. When a single web service cannot solve a given task, several web services are composed. Composition can be done either statically at design time or dynamically at runtime. Dynamic composition is more suitable for business applications where in business policies and user requirements frequently changes. Interleaved dynamic composition and execution of services is beneficial for adapting to changing user preferences. One of the main issues in such a scenario is that whether the component services that are composed operate according to the business rules specified. Safety, liveness and deadlock freedom properties of a composition depend on the behavior of individual services. Existing modeling techniques capture these properties and perform model checking only statically. Hence in this work, a two level model verification approach has been proposed to verify the correctness of dynamically composed services.